2018
DOI: 10.1002/jcp.26407
|View full text |Cite
|
Sign up to set email alerts
|

Comparative peptidomic profile between human hypertrophic scar tissue and matched normal skin for identification of endogenous peptides involved in scar pathology

Abstract: Endogenous peptides recently attract increasing attention for their participation in various biological processes. Their roles in the pathogenesis of human hypertrophic scar remains poorly understood. In this study, we used liquid chromatography-tandem mass spectrometry to construct a comparative peptidomic profiling between human hypertrophic scar tissue and matched normal skin. A total of 179 peptides were significantly differentially expressed in human hypertrophic scar tissue, with 95 upregulated and 84 do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…In the present data, more than one peptide was derived from the same precursor protein, and many peptides came from the same segment of a precursor protein, exhibiting a ladder-like distribution (Figure ). Similar phenomena have been reported by other studies, which might indicate the specificity of cleavage and proteolytic enzyme activity under salt stress. It is known that some bioactive peptides are contained in precursor proteins and do not show related activity before proteolytic cleavage. , However, when organisms are exposed to external stimuli, they appear to adjust peptide expression levels in response to external stimuli by altering the type and activity of proteases. , …”
Section: Resultssupporting
confidence: 91%
“…In the present data, more than one peptide was derived from the same precursor protein, and many peptides came from the same segment of a precursor protein, exhibiting a ladder-like distribution (Figure ). Similar phenomena have been reported by other studies, which might indicate the specificity of cleavage and proteolytic enzyme activity under salt stress. It is known that some bioactive peptides are contained in precursor proteins and do not show related activity before proteolytic cleavage. , However, when organisms are exposed to external stimuli, they appear to adjust peptide expression levels in response to external stimuli by altering the type and activity of proteases. , …”
Section: Resultssupporting
confidence: 91%
“…Furthermore, peptides recognized as biomarkers tend to be clustered around certain regions, as seen in Table 1 . As mentioned, the hemoglobin subunit beta region (112–147) stands out, having been thoroughly described for its various antimicrobial properties both in vitro and in vivo , but also as a biomarker for several inflammatory conditions such as hypertrophic scar formation ( 33 ), acute severe pancreatitis ( 37 ) and transitional cell carcinoma ( 41 ). In order to estimate the presence of the various peptides and regions in the different groups, spectral counting was performed.…”
Section: Resultsmentioning
confidence: 99%
“…A multitude of peptides, such as recombinant human IL10-RGD (rhIL10-RGD), transforming growth factor beta peptide antagonists, and P144 peptide, have been thoroughly studied in the treatment of hypertrophic scar [ 72 , 73 ]. However, in hypertrophic scar pathogenesis, the part played by endogenous peptides has seldom been studied.…”
Section: Proteomicsmentioning
confidence: 99%
“…However, in hypertrophic scar pathogenesis, the part played by endogenous peptides has seldom been studied. Li et al conducted a comparative peptidomics study of human hypertrophic scar tissue with matched normal skin to investigate how endogenous peptides are involved in scar formation by using liquid chromatography tandem mass spectrometry (LC-MS/MS) [ 72 ]. Using LC-MS/MS, Li et al found a total of 1,697 nonredundant peptides in hypertrophic scar tissues and the matched normal skin.…”
Section: Proteomicsmentioning
confidence: 99%